Penerapan komunikasi dan solusi yang tepat dalam mengatasi masalah operasional: Studi kasus pada toko buah di Desa Sumberejo Kota Batu - Pratama, Mohammad Aditya (Maliki Interdisciplinary Journal, 2024)
UMKM are an activity that is generally carried out by people in Indonesia. With the large number of UMKM that exist in Indonesia today, it will be very profitable to overcome the problem of proverty. Apart from that, a lot of state income is also obtained from these UMKM activities. Of course, UMKM activities are not far from public relations activities. Public relation is also an acitivity that is directly related to humans or the general public. This is the same as UMKM activities, which in fact are buying and selling activities. Of course, in carrying out buying and selling activities, beginners often encounter obstacles such as operational problems and other obstacles. Therefore, the solution to these obstacles can be overcome by carrying out exercise so that mistakes do not occur in carrying out these activities.